Causes of hand injuries among pianists: a case study / Asma Syahirah Abdul Muta’ali - Abdul Muta’ali, Asma Syahirah (Faculty of Music, 2016)
The purpose of this study is to discuss some of the different types of hand injuries faced by piano students from different universities. This research is to determine what are the causes of hand injuries suffered by these piano students and how it has affected their performances. The hand injuries might has an after effects or permanent damage. Since Malaysia is lacking of specialist in musicians' injuries, this study is to find out how these piano students find ways to overcome their hand injuries. Other than that, this study is also to look into the background and the environment of each student whether it could lead to hand injuries.